Hasan al-Banna and Islamic Education Politics: Weaving the Mind, Heart, and Spirit of Struggle from Egypt to the World - Kurniawan, Syamsul; ., Maimunah (UI Scholars Hub, 2025)
This article examines Hasan al-Banna's thoughts on Islamic education politics, with a focus on the integration of three main dimensions: heart, mind, and the spirit of struggle, which form the foundation of the educational system he proposed from Egypt for the world. Through the Ikhwanul Muslimin movement, which originated in Egypt, al-Banna introduced an education that unified spirituality, intellectualism, and political struggle into a cohesive whole. This study employs the Atomic Habits theory by James Clear (2019), which emphasizes small, consistent changes that lead to significant impacts, to understand how al-Banna’s ideas on Islamic education can be viewed as a process of habit formation and identity development. The qualitative approach with library research methods explores primary and secondary sources, including the works of Hasan al-Banna and contemporary literature that examines the context of Egypt and the Middle East. The analysis results show that, according to al-Banna, education is not merely the transfer of knowledge, but a process of shaping strong character, critical thinking, and an orientation towards the welfare of the ummah as well as social-political struggle. The uniqueness of this study lies in the integration of religious education, general knowledge, and politics within a framework that advocates for the unity of the Muslim ummah in the context of social-political challenges in Egypt and the Middle East. The significance of this paper provides a new perspective for building Islamic education that unites the spiritual, intellectual, and socio-political dimensions, as well as its relevance to the dynamics of education and politics in Egypt and the modern Muslim world.